Gallbladder Agenesis: A Case Report of an intraoperative diagnosis - Carvalho, Ana Cristina Silva (2017)
Introduction: Agenesis of the gallbladder is a rare congenital anomaly occurring in 10 to 65 per 100 000 people. Patients are usually asymptomatic and the diagnosis is made as an incidental finding during another abdominal surgery or at autopsy. The presence of biliary symptoms and a misleading ultrasound study can lead to unnecessary surgery. Case Presentation: We present a 43-year-old female proposed to laparoscopic cholecystectomy for suspected symptomatic gallbladder lithiasis in the clinical and radiological studies prior to surgery. During operation the gallbladder was not identified and the procedure was terminated for further diagnostic procedures. The post-operative study with magnetic resonance cholangiopancreatography confirmed the diagnosis of gallbladder agenesis. Conclusion: The difficulty in diagnosing the absence of gallbladder in the preoperative period can be explained by the infrequency of the condition and consequent low index of suspicion for agenesis when interpreting imaging findings. Surgeons must be aware of this condition and when gallbladder isn’t visualized at laparoscopy decide between convert surgery to open procedure or abort surgery and continue study with other imaging techniques. The latter is a good option, allowing a better characterization of biliary anatomy as well as avoiding morbidity of a laparotomy.